Enhancement of Biogas Production Using Co-Substrates In Anaerobic Digesters for Medium Size Dairy Farms - Sauve, Terrence (University of Ottawa (Canada), 2010)
The use of co-substrates can significantly enhance biogas production from manure while helping to treat and dispose of high carbon organic wastes from the food processing industry and municipalities. This thesis will focus on the experimental setup and results collected at the University of Guelph -- Campus d'Alfred from a series of Biochemical Methane Potential assays and six 30 L semi-continuous anaerobic digesters operating under mesophilic conditions. The co-substrates investigated during the study include: corn silage, canola meal, whey, glycerine and dissolved air floatation sludge. The use of liquid dairy manure proved to be beneficial for the anaerobic digestion process by supplementing necessary buffering capacity, nitrogen, micro and macro elements for the co-digestion of high carbon organic wastes. Biochemical Methane Potential assays of the co-substrates increased the biogas yield from 5 to 250%. When these co-substrates were elaborated in semi-continuous pilot digesters, volumetric biogas production increased two to three-folds in relation to liquid dairy manure.
Keywords: Engineering, Agricultural.; Engineering, Environmental.